Design of a Stem Cell-Based Therapy for Ependymal Repair in Hydrocephalus Associated With Germinal Matrix Hemorrhages - Rodríguez-Pérez, Luis Manuel; Ojeda-Pérez, Betsaida; López-de-San-Sebastián, Javier; García-Bonilla, María; González-García, Marcos; Fernandez-Muñoz, Beatriz; Sánchez Pernaute, Rosario; García-Martín, María L.; Domínguez-Pinos, Dolores; Cárdenas García, Casimiro; Jiménez-Lara, Antonio Jesús; Páez-González, Patricia (AHA/ASA Journals, 2024)
BACKGROUND: In preterm birth germinal matrix hemorrhages (GMHs) and the consequent posthemorrhagic hydrocephalus (PHH), the neuroepithelium/ependyma development is disrupted. This work is aimed to explore the possibilities of ependymal repair in GMH/PHH using a combination of neural stem cells (NSCs), ependymal progenitors (EpPs), and mesenchymal stem cells (MSCs). METHODS: GMH/PHH was induced in 4-day-old mice using collagenase, blood, or blood serum injections. PHH severity was characterized 2 weeks later using magnetic resonance, immunofluorescence, and protein expression quantification with mass spectrometry. Ependymal restoration and wall regeneration after stem cell treatments were tested in vivo and in an ex vivo experimental approach using ventricular walls from mice developing moderate and severe GMH/PHH. The effect of the GMH environment on EpP differentiation was tested in vitro. Two-tailed Student t or Wilcoxon-Mann-Whitney U test was used to find differences between the treated and nontreated groups. ANOVA and Kruskal-Wallis tests were used to compare >2 groups with post hoc Tukey and Dunn multiple comparison tests, respectively. RESULTS: PHH severity was correlated with the extension of GMH and ependymal disruption. GMH/PHH hindered the survival rates of the transplanted NSCs/EpPs. New multiciliated ependymal cells could be generated from transplanted NSCs and more efficiently from EpPs. Blood and TNFα negatively affected ciliogenesis in cells committed to ependyma differentiation. Pretreatment with MSCs improved the survival rates of EpPs and ependymal differentiation while reducing the edematous and inflammatory conditions in the explants. The effectiveness of this therapeutical strategy was corroborated in vivo. CONCLUSIONS: In GMH/PHH, the ependyma can be restored and edema decreased from either NSCs or EpP transplantation in vitro and in vivo. MSCs pretreatment improved the success of the ependymal restoration.
Keywords: Hidrocefalia - Tratamientos; Células madre neurales; Modelos animales en investigación; Edema; Ependyma; Hydrocephalus; Mesenchymal stem cells; Neural stem cells